The influence of physical activity in the progression of experimental lung cancer in mice - Paceli, Renato Batista; Cal, Rodrigo Nunes; Ferreira dos Santos, Carlos Henrique; Cordeiro, Jose Antonio; Neiva, Cassiano Merussi [UNESP]; Nagamine, Kazuo Kawano [UNESP]; Cury, Patricia Maluf (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Lung cancer is one of the most incident neoplasms in the world, representing the main cause of mortality for cancer. Many epidemiologic studies have suggested that physical activity may reduce the risk of lung cancer, other works evaluate the effectiveness of the use of the physical activity in the suppression, remission and reduction of the recurrence of tumors.The aim of this study was to evaluate the effects of aerobic and anaerobic physical activity in the development and the progression of lung cancer.Lung tumors were induced with a dose of 3 mg of urethane/kg, in 67 male Balb - C type mice, divided in three groups: group 1_24 mice treated with urethane and without physical activity; group 2_25 mice with urethane and subjected to aerobic swimming free exercise; group 3_18 mice with urethane, subjected to anaerobic swimming exercise with gradual loading 5-20% of body weight. All the animals were sacrificed after 20 weeks, and lung lesions were analyzed.The median number of lesions (nodules and hyperplasia) was 3.0 for group 1, 2.0 for group 2 and 1.5-3 (p = 0.052). When comparing only the presence or absence of lesion, there was a decrease in the number of lesions in group 3 as compared with group 1 (p = 0.03) but not in relation to group 2. There were no metastases or other changes in other organs.The anaerobic physical activity, but not aerobic, diminishes the incidence of experimental lung tumors. (c) 2012 Elsevier GmbH. All rights reserved.
Keywords: Physical activity; Experimental lung cancer; Aerobic exercise; Anaerobic exercise